Luxury fashion brands and the female body: Absence of Corporate Social Responsibility in Instagram advertising - Sánchez-Labella Martín, Inmaculada (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2021)
This work focuses on analyzing whether luxury fashion brands, considered to Forbes magazine 2018, contribute with social responsibility for the sake of female inclusion. For this, we have been taken as a sample the profiles of the most influential Instagrammers of size XL at the international level in 2019, published by the magazine Trendencias (2019). Applying a qualitative-descriptive methodology, it has been shown that luxury fashion brands that are advertised on Instagram induce the consolidation of a social system in which perfect bodies prevail, according to the traditional canon of beauty